The Emergence of the JD in the Australian Legal Education Marketplace and its Impact on Academic Standards - Donna Cooper; Sheryl Jackson; Rodalind Mason; Mary Toohey (Legal Education Review)
Theoretical topics play a significant role in the law curriculum. There is, however, little scholarly literature on the pedagogical challenges of teaching theory to law students. This article takes some preliminary steps towards filling this gap. The article begins by discussing the place of theory in legal education. It then outlines some strategies for structuring theoretical modules in law courses and promoting student engagement with the material.